Analysis of reported animal abuse in Campo Magro, Paraná, Brazil - Wolf, Larissa Rachel; Galdioli, Lucas; Brugnerotto, Michele; Ramos, Mateus Gemelli; Garcia, Rita de Cassia Maria (Brazilian Journal of Veterinary Research and Animal Science, 2022)
Animal abuse is a criminal offense in Brazil and can be dealt with by several government agencies, including municipal ones. Cases of animal abuse reported to the Department of Health Surveillance, of the Municipal Health Secretariat of Campo Magro, Paraná, Brazil, between March of 2019 and December of 2020 were analyzed to assess the most common forms of abuse and animals involved. A total of 140 complaints were received in this period; 132 were investigated, of which 81 were considered authentic. The most common form of abuse was neglect 64.2% (52/81). Cases of neglect were further classified into four types (although cases may be classified with more than one type), resulting in 106 classifications of neglect. Behavioral neglect was the most common form of neglect 33.9% (36/106). As more than one animal could be involved in each report, the 81 authentic cases involved a total of 471 animals. Dogs were the species most commonly affected 78.5% (370/471). The vast majority of animal abuse was perpetrated against adult animals. Statistically significant correlations were found between the sex and age of dogs and abuse and between species and the different forms of abuse for dogs and cats.